Association between hoof pathologies and productive indicators in lactating cows - Rodríguez, María Inés (2021)
The aim of this study was to evaluate the association between hoof pathologies and indicators of dairy production in dairy farms in the department of Caaguazú, Paraguay. Fifty cows reared in compost bed barns were evaluated, with hoof pathologies diagnosed during the descending phase of lactation. The type of hoof pathology, location, evolution, milk production, fat content, protein content and somatic cell count (SCC) were evaluated between September 2019 and January 2020. The Friedman test was used to detect statistical differences between groups according to the lactation days: Category 1, 92-137; Category 2, 138-182; and Category 3, 183-227 days of lactation. The sole and the interdigital area registered a higher frequency of pathologies; while, the white line, wall and heel the least casuistry. The frequency in the pelvic limb was different in Category 3 with the lowest count (p˂0.05), while there were no differences between the other two categories. The frequency of animals with low, medium and high levels in the productive variables did not differ between the groups. The multiple correspondence analysis detected an association between category 3, sole hemorrhage, mild evolution, and high fat and protein levels. Those in category 2 were linked to interdigital phlegmon, severe evolution and low and medium levels of protein and fat, respectively. The pathology with the least impact on production, due to the lower SCC and the highest quantity of milk produced, was white line disease. In contrast, the sole ulcer of severe evolution was associated with the highest SCC and the lowest amount of milk produced.